PROFITABILITY OF CHARCOAL MARKETING IN GUSAU METROPOLIS, ZAMFARA STATE, NIGERIA - Gusau, S. M.; Gusau, Y. M.; Abbas, A.; Sani, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assesed the profitability of charcoal marketing in Gusau metropolis, Zamfara State, Nigeria. Simple random sampling technique was used in selecting 50 charcoal marketers from the study area. Data were obtained through the administration questionnaire and analyzed using descriptive statistics, Marketing margin, Rate of return ratio and net marketing margin. The findings revealed that charcoal marketing was predominantly dominated by married males. All (100%) of the respondents were male, 62% of the respondents were in the active age of between 31-40 years. The result shows that (100%) of the respondents were registered members of charcoal marketers association. With regards to marketing margin analysis the study revealed that charcoal marketing was profitable with a net marketing margin N2800/100kg bag and N1800/100kg bag at peak and off-peak period. The result also revealed a net return of N4600, indicates the magnitude of the returns in charcoal marketing. The peak period had N2800 profit while the off-peak period of marketing had N1800, with rate of return ratio of (0.28) and (0.26) indicates that rate of return to capital of 28 kobo at peak period and 26 kobo at off-peak period for every naira invested in charcoal marketing in the study areas. The study concluded that charcoal marketing in the study area is profitable as it gives higher returns per naira invested during the peak period and off period of marketing. It is recommended that charcoal marketer’s association leaders should be very active and partner with financial institutions so as to easily have access to loans at reduced interest rate to help the charcoal marketers to have more capital base and in turn improve their business and their living standard. Provision of alternative livelihood systems for charcoal marketers and regulation of the charcoal marketing by the government will help manage the forest resources sustainably.